IDENTIFIKASI DAN UJI KUALITAS PIGMEN KULIT BUAH NAGA MERAH (HYLOCAREUS COSTARICENSIS) PADA BEBERAPA UMUR SIMPANDENGAN PERBEDAAN JENIS PELARUT - Elfi Anis Saati (Jurnal Gamma, 2010)
An alternative excavation of natural materials that could potentially be used as a substancedyes, continue to be made, including the skin of red dragon fruit. Because the red dragon fruit latelya lot of public interest, skin which amounts to 30-35% is often just discarded as waste only.In an effort to use the red dragon fruit peel waste that is not optimal, to increase the economicvalue of the skins of red dragon fruit and power use for the community.The goal is to mengetehaui type of pigment and pigment quality of dragon fruit red on someshelf with different types of solvents.This research used Randomized Design Group (RAK) Factorial consisting of two factors I;comprised of over 4 levels; factor II consisted of 3 level. Factor I: The Fruit Store (S), fresh (day0), the shelf life of fruit 2 days, 4 days and 8 days, whereas the second factor: the type of solvent(L), namely aquades; combination aquades and citric acid (9:1), and a combination Eeanol 1N andcitric acid (9:1).The results showed that the skin of red dragon fruit (Hylocereus costaricensis) containinganthocyanin type ramnosil sianidin 3-glucoside 5 - glucoside, based on Rf values (retrogradationfactor) of 0.36 to 0.38 and maximum absorbance at a wavelength with ë = 536.4 nm. Combinationtreatment S2P2 (the shelf life of fruit 4 days with solvent water and citric acid) produce anthocyaninpigments of red dragon fruit skin with the best quality, with a pH value of 1.91; the brightness (L)25.60; level of redness (a +) 6.97; the yellow (+ b) 0.50, 0.363 pigment absorbance; levels ofanthocyanin 1.1 mg/100ml; total dissolved solids 66.52% and 10.02% yield.